GAMBARAN PERILAKU MENGGOSOK GIGI TERHADAP KEBERSIHAN GIGI DAN MULUT PADA USIA SEKOLAH DASAR - Nurhamidah, Nurhamidah; Netty Jojor Aritonang; Asmawati; Intan Aritoanng (Poltekkes Kemenkes Medan, 2024)
Dental health efforts need to be reviewed from environmental aspects, knowledge, education, public awareness and handling of dental health including prevention and treatment. But most people ignore the overall dental health conditions. This study aims to determine the correlation between tooth brushing behavior on dental and oral hygiene in elementary school children. The type of research used was a systematic review research. Based on the results of the study, it was found that the characteristics of the condition of dental and oral hygiene were GOOD, 50% of the articles with the criteria of MEDIUM dental and oral hygiene, and 30% of the articles with the criteria of POOR dental and oral hygiene. From this systematic review, it proved that the condition of dental and oral hygiene obtained data that 20% of articles with good dental and oral hygiene criteria, 50% articles with moderate dental and oral hygiene criteria, and 30% articles with poor oral hygiene criteria, so it can be concluded that Elementary School Children must further improve their behavior in maintaining dental and oral health by brushing their teeth regularly so that their dental and oral health will be better.